Understanding the challenges of emergency remote teaching for students at a South African university of technology post-COVID-19 - Molokomme, Radiakga Thabang; Klerk, Charmaine de; Shube, Innocentia (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic forced higher education institutions (HEIs) to transition from traditional face-to-face learning to emergency remote teaching (ERT). This study explores the challenges faced by fourth-year students at the University of Technology (UoT) in Gauteng during this transition, particularly in the post-pandemic context. This study addresses critical gaps in the existing literature on ERT challenges experienced by students at a South African UoT, particularly focusing on the contextual factors and diverse student populations. Underpinned by the Technological Determinism Theory (TDT) and Constructivist Learning Theory (CLT), the study examines how technology shaped students’ learning experiences and how they constructed knowledge in an online environment. Using a phenomenological qualitative approach, data were collected through semi-structured interviews with twelve fourth-year students who experienced both face-to-face and online learning. Thematic analysis revealed key challenges, including unreliable internet connectivity, lack of digital resources, and disruptions caused by load shedding. The findings emphasize the need for HEIs, especially UoTs, to enhance internet infrastructure, provide adequate digital resources, and implement robust training programs for students and staff. This study contributes to the growing body of research on post-COVID-19 ERT challenges in developing countries and provides practical recommendations for enhancing online learning implementation.